2009
DOI: 10.1038/cdd.2009.54
|View full text |Cite
|
Sign up to set email alerts
|

The late stages of autophagy: how does the end begin?

Abstract: Autophagy is a catabolic cellular process involving dynamic membrane rearrangement. Here, we review the understanding of autophagy, focusing on the late stages of the process, from the closing of the autophagosome to fusion with the lysosome. We propose the Reverse fusion model, for the closing autophagosome. In this model, autophagosome closure proceeds in a topologically similar but reverse order to membrane fusion during the escape of influenza virus from the endosome. This dynamic process is thought to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
124
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(129 citation statements)
references
References 52 publications
5
124
0
Order By: Relevance
“…Autophagy requires the clearance of autophagosomes and their cargo upon fusion with lysosomes. 5,6 It is suggested that this fusion is regulated by several Rab proteins and soluble N-ethylmaleimidine-sensitive factor attachment protein receptors (SNAREs). 4,6,7 Similarly in case of bi-directional ER-Golgi transport the tethering of the COPII-coated vesicles at Golgi membrane takes place in anterograde transport, when in retrograde transport COPIcoated vesicles are tethered at ER membrane.…”
mentioning
confidence: 99%
“…Autophagy requires the clearance of autophagosomes and their cargo upon fusion with lysosomes. 5,6 It is suggested that this fusion is regulated by several Rab proteins and soluble N-ethylmaleimidine-sensitive factor attachment protein receptors (SNAREs). 4,6,7 Similarly in case of bi-directional ER-Golgi transport the tethering of the COPII-coated vesicles at Golgi membrane takes place in anterograde transport, when in retrograde transport COPIcoated vesicles are tethered at ER membrane.…”
mentioning
confidence: 99%
“…13 Subsequently, by fusing with endosomal/lysosomal compartments, the autophagosome matures into the autophagolysosome, wherein the substrate is degraded by acid hydrolases. 14 Autophagy is triggered by the so-called beclin-1/PI3kIII interactome, a macro-complex participated by several other proteins, which locates in the proximity of the trans Golgi network. 12 The autophagy process is finely tuned by sensors of nutrients and energy available.…”
mentioning
confidence: 99%
“…to function in the later phase (Fujita et al, 2008a;Noda et al, 2009). To determine whether Atg14L is involved in the initial phase of autophagosome formation or at a later phase, we observed the GFP-DFCP1 distribution pattern before and after autophagy-inducing nutrient starvation conditions.…”
Section: Introductionmentioning
confidence: 99%